ANALISIS DAN EFEKTIVITAS PEMUNGUTAN PAJAK DAERAH DI INDONESIA - Fiyar Hanto; Reniati Reniati; Etty Puji Lestari (Jurnal Bina Bangsa Ekonomika, 2023)
The increase in the realization of the regional tax budget from year to year cannot be used as a guideline in measuring the success of tax collection that has been carried out by local governments. Therefore, it is necessary to calculate the contribution and effectiveness of local taxes and levies so as to assist local governments in measuring the success of collecting local taxes and regional levies. The purpose of this article is to analyze the reconciliation of local tax collection in Indonesia, especially at the Regional Finance Agency of Pangkalpinang City. The method used is quantitative descriptive. The results of this study show that the average level of effectiveness of local tax collection in Pangkalpinang City in 2011-2020 can be categorized as very effective. This Regional Original Revenue is contributed by 4 types of taxes, namely restaurant tax, street lighting tax, land and building rights acquisition duty and land and building tax. Meanwhile, the growth rate of local taxes fluctuates. However, although still relatively effective, improvements are still needed so that tax revenue increases even more